INNATE IMMUNITY: MECHANISMS OF REALIZATION AND PATHOLOGICAL SYNDROMES. PART II - P.F. Litvitsky; T.G. Sinel’nikova (Вопросы современной педиатрии, 2009)
The role and mechanisms of realization of biomechanical, physical, chemical and biological factors of system of non-specific defense of organism are discussed in this article. Authors characterize the main cell and humoral factors of this system; analyze etiology, pathogenesis and main signs of syndromes of insufficiency of immunosurveillance of organism, developing as a result of disorders of inborn immunity mechanisms.Key words: biomechanical and physical, chemical factors of defense, natural killers, cytolysis mechanisms, syndrome of inborn immunity insufficiency.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2009;8(2):59-67)